Fermentation of tocino - Santiago, Evelyn S.; Sevilla, Ursula L. (1975.)
Fermentation of "tocino" was allowed to take place spontaneously at two different storage conditions, one at room temperature (20°-32°C), and another at refrigerator temperature (15°-18°C). Microbiological examinations, pH, titratable acidity, and residual sugar determinations were carried out at specified intervals. Results showed that fermentation at room temperature was much faster than fermentation at refrigerator temperature. It was also shown that during the course of the fermentation, the pH and the residual sugar of the fermenting meat decreased while the amount of lactic acid increased. Sensory evaluation of "tocino" at different stages of the fermentation was also conducted to determine how the sensory qualities of the meat were affected by the fermentation. Analysis of variance revealed no significant difference in color, odor, and flavor of the products, but showed a significant difference on their general acceptability. Total scores obtained on the evaluation for general acceptability indicated that "tocino" fermented for one day at room temperature obtained the highest score, while unfermented "tocino" obtained the lowest score.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Meat -- Preservation